Volume 1: Fluid Mechanics 2019
DOI: 10.1115/ajkfluids2019-5463
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Nozzle Orientation Effects on Mixing Characteristics of Elliptic Triple Free Jets

Abstract: An experimental investigation of nozzle orientation effects on turbulent characteristics of elliptic triple free jets was carried out for three nozzle configurations. The first configuration had all three nozzles oriented along the minor plane (3_Minor), the next had two nozzles oriented along the minor plane and one along the major plane (2_Minor_1_Major) and the last configuration had one nozzle oriented along the minor plane and two along the major plane (1_Minor_2_Major). The experiments were conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Different PC values for Single Ellipse Major and Single Ellipse Minor could result from separate simulations of elliptical jet with orientation, which could lead to a numerical discrepancy of results. Similar results for the elliptical jet with orientation are reported by Morris et al 16,30 The potential core length of the elliptical jets is 8.6% shorter than that of the single circular jet. These results agree with Mi and Nathan et al 3 for the elliptical nozzle case.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Different PC values for Single Ellipse Major and Single Ellipse Minor could result from separate simulations of elliptical jet with orientation, which could lead to a numerical discrepancy of results. Similar results for the elliptical jet with orientation are reported by Morris et al 16,30 The potential core length of the elliptical jets is 8.6% shorter than that of the single circular jet. These results agree with Mi and Nathan et al 3 for the elliptical nozzle case.…”
Section: Resultssupporting
confidence: 89%
“…It is also noted that the difference between the decay rates of Twin Ellipse Major and Twin Ellipse Minor is not very drastic, so it can be concluded that the orientation did not affect the velocity decay rate significantly. Similar observations were made by Mi and Nathan 3 and Morris et al 30 in their studies.…”
Section: Mean Velocity Decay Ratesupporting
confidence: 87%
See 1 more Smart Citation
“…More atypical solutions in this regard have also been presented, e.g. for an elliptical nozzle [33], [34] or a lobed nozzle [35], [36]. The diffuser shape also affects the number of symmetry axes that can be distinguished in a jet.…”
Section: Introductionmentioning
confidence: 99%